Checklist of gastropods from the exclusive economic zone (EEZ), Sarawak, Malaysia - Wan Zabidii, Wan Morni; Siti Akmar Khadijah, Ab Rahim; Richard, Rumpet; Jamil, Musel; Ruhana, Hassan (Penerbit Universiti Sains Malaysia, 2017)
This study provides the first marine gastropod checklist from the Sarawak Exclusive Economic Zone (EEZ). Gastropod samples were collected from selected stations in the Sarawak EEZ using an otter trawl net with a stretched mesh size of 38 mm at the cod end. The trawling operations were conducted more than 12 nautical miles from the coast, and the area was divided into three depth strata: I) 20–50 m, II) 50–100 m and III) 100–200 m. A total of 23 gastropod species were identified during the two-month sampling period from 16 August until 6 October 2015, representing 8 superfamilies, 15 families and 20 genera. Superfamily Tonnoidea was represented by 7 species, followed by Muricoidea (5 species), Cypraeoidea (4 species), and Buccinoidea and Conoidea (both with 2 species). Other superfamilies were represented by a single species. Only 3 species were obtained in 2 depth strata, namely Melo melo, Murex aduncospinosus and Tonna galea. In addition, 9, 13 and 4 species of gastropods were found in strata I, II and III, respectively. The information on gastropod distributions at different depth strata in the Sarawak EEZ could be useful in updating the Malaysian species diversity database